Analysis of the Effectiveness of Tax Deduction Reporting in the SP2D Treasury Sector of the Manado City BKAD - Randy Kaparang; Stevie Kaligis; Fanesa Esalia Minanda Syaefudin; Alpindos Toweula (INVENTORY: JURNAL AKUNTANSI, 2026)
Transparent, effective, and accountable regional financial management is one of the main pillars in realizing good governance. One important aspect of this is the process of reporting tax deductions on the Fund Disbursement Order (SP2D) carried out by the Regional Finance and Asset Agency (BKAD) of Manado City. This study aims to assess the effectiveness of tax deduction reporting on SP2D while identifying the challenges encountered in its implementation. The method used is qualitative descriptive, with data collection through observation, interviews, and documentation. The results of tax reporting generally comply with regulations; however, its effectiveness is not yet optimal due to challenges such as limited human resources, delayed reporting, and the lack of integration between the regional financial system and the national tax system. These findings emphasize the need to enhance human resource capacity, optimize an integrated reporting system, and synchronize data across agencies. This study contributes to strengthening the understanding of the effectiveness of public sector tax reporting and provides strategic recommendations for continuous improvement. Key recommendations include technical training, updating information systems, and leveraging information technology to enhance the accuracy and timeliness of local tax reporting.